Etos Kerja Perempuan Madura (Studi terhadap Perempuan Madura yang Berdagang di Kelurahan Dalam Bugis Pontianak Timur) - Arkanudin, Arkanudin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Although Madurese women in this village are relatively small, they often carry out various economic activities, especially in the informal sector, which go unnoticed by others. The purpose of the research is to find out the work ethic, and motivation of Madurese women to trade. The results of observations, interviews, and document studies were processed descriptively with a qualitative approach. The results showed that Madurese women choose to work as traders because they do not have special skills, making it difficult to find other jobs. Madurese women have diverse work ethics, including hard work, responsibility, simple living, as well as tenacity and persistence in running their business.